In vitro synergistic effect of sumac in combination with cloxacillin, cephalexin, and vancomycin against clinical isolates of methicillin-resistant staphylococcus aureus: MRSA Inhibition: Sumac and Antibiotic Combinations - Khanlarbeik, Meysam; Sheikholeslami, Samin; Jamalifar, Hossein; Eslami, Solat; Monsef-Esfahani, Hamid Reza; Fazeli, Mohammad Reza; Ahmadian-Attari, Mohammad Mahdi (Iranian Journal of Pharmaceutical Sciences, 2025)
Methicillin-resistant Staphylococcus aureus (MRSA) has been associated with substantially higher morbidity and mortality rates due to the acquired multidrug resistance. Accordingly, there exists a growing demand for development of natural products as alternative treatments or combination drug therapies against this infection. This study aimed to assess the synergistic effect of sumac in combination with clinically important antibiotics against ten clinical isolates of MRSA. A total of 50 staphylococci clinical isolates were screened for susceptibility to antibiotics, and 10 isolates were selected for further studies. The disc diffusion method (DDM) was used to screen the synergy effects of the sumac extract with 7 antibiotics against clinical isolates of MRSA. The broth microdilution method determined the minimum inhibitory concentration (MICs) of sumac extract and three selected antibiotics. The synergistic effect of the sumac extract and three antibiotics was assessed and evaluated using checkerboard dilution methods. The three antibiotics, i.e., cloxacillin, cephalexin, and vancomycin, showed considerable synergistic effects with sumac extract based on DDM. The MICs of sumac against ten clinical MRSA isolates ranged from 1600 to 6400 µg/ml. In the checkerboard dilution method, sumac markedly reduced the MICs of the antibiotics cloxacillin and cephalexin, and a significant synergistic effect was recorded by sumac in combination with these two antibiotics. Our results demonstrated that sumac extract enhances the antibiotic potential against MRSA in vitro conditions. This study suggested that sumac, in combination with antibiotics, could lead to the development a new combination of antibiotics against MRSA.